1982
DOI: 10.1007/bf00347871
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous metal binding proteins in relation to the differences in absorption and distribution of mercury in newborn and adult rats

Abstract: Abstract. Both in the ilatestinal copper complex and hepatic zinc-thionein of the newborn rat provide immediately available, high-affinity binding sites for Hg 2+. Retention of orally administered Hg 2+ in the gastrointestinal tract is much greater in the 5-day old rat than in the weanling and accounts for most (70-90%) of the body burden at 18 h. At a dose level of 790 ~tg Hg2+/kg body weight, 41% of the Hg 2 § retained in the gastrointestinal tract of the newborn animal is located in the soluble fraction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 16 publications
(22 reference statements)
3
6
0
Order By: Relevance
“…The retention in the liver was slightly lower in sucklings than in older rats. This supports the conclusions made by several authors that the higher liver metallothionein concentration (18,19) does not influence cadmium distribution (15,20,21). The higher brain retention found in sucklings is in agreement with several previously published results (11,22).…”
Section: Effect Of Various Foods On Cadmium Retention and Distributionsupporting
confidence: 93%
See 1 more Smart Citation
“…The retention in the liver was slightly lower in sucklings than in older rats. This supports the conclusions made by several authors that the higher liver metallothionein concentration (18,19) does not influence cadmium distribution (15,20,21). The higher brain retention found in sucklings is in agreement with several previously published results (11,22).…”
Section: Effect Of Various Foods On Cadmium Retention and Distributionsupporting
confidence: 93%
“…Immaturity obviously influences uptake from blood to organs as well as elimination and perhaps age-related differences in the binding affinities and/or content of metal carrier proteins. These and other possibilities are discussed in detail elsewhere (21,(37)(38)(39).…”
Section: Effect Of Various Foods On Cadmium Retention and Distributionmentioning
confidence: 98%
“…28,36,[54][55][56][57] In line with this, it was previously demonstrated that preexposure to ZnCl 2 prevents the renal damage and the inhibitory effect in the renal δ-ALA-D activity induced by HgCl 2 in young rats concomitantly to the increase of MT levels. 28,34 Because the sensitivity of developing animals to various compounds (including metals) may differ from that observed in adults, [19][20][21][22] we also evaluated the effects of metals in pups via maternal milk. The transport of inorganic mercury into milk was previously demonstrated in rats by Sundberg et al 58 and in guinea pigs by Yoshida et al 59 Indeed, Sundberg et al 58 demonstrated that mercury concentration in milk is linearly correlated to the levels in the kidney of suckling pups after exposure to mercury via milk.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of developing animals to various compounds (including metals) may differ from that observed in adults, [19][20][21][22] making the study of metal effects on developing organisms important. In fact, young animals, mainly during the first days after birth, seem to be more sensitive than adults to toxic agents.…”
Section: Introductionmentioning
confidence: 99%
“…An ionized compound will not enter the CNS as readily as a compound that is not ionized, in which case it will enter the brain at a rate proportional to its lipid:water partition coefficient (171). For example, methyl mercury enters the brain much more readily than inorganic mercury (110,172).…”
Section: Practical Considerations In the Experimental Design Of Pharmmentioning
confidence: 99%